A conceptual model of Russia’s long-term development amid new challenges - Evgeny V. Balatsky; Nataly A. Ekimova (Управленец)
To date, there is a lack of theoretical or practical frameworks for a global view of Russia’s development over the upcoming two or three decades. At the same time, it is especially urgent to tackle this problem due to emerging geopolitical challenges. The study proposes a conceptual model of the development of the Russian Federation. The foundation of research resides in the concept of synergy that assumes uniting individual elements of long-term policy into a solid consistent whole with emergent properties. Structural-logical analysis and synthesis are used. The development model is rooted in three cross-cutting principles that permeate through the entire economic system: economies of scale, the principle of congruence, and the enhanced model of the country’s prosperity. They organize the national development strategy, shed light on the state’s competitive advantages and pathways to achieve goals. The architecture of the conceptual model comprises a theoretical component covering state ideology and a functional component incorporating demography, economy, and technology. Ideology section suggests formulating a new state ideology and defining the country’s economic system. Demography section involves a demographic manoeuvre ensuring transition towards demographic expansion, demographic expansion based on institutional, economic, and cultural reforms, and migration control for preserving national identity. Economy section prioritizes antifragility of the economy, introduction of a multi-level system of selective economic management and a model of people’s capitalism. Technology section implies a technological breakthrough using current industrial capacities, monetary incentives for nascent industries, and large-scale technological diffusion. Pursuing this strategy will solve the country’s key socio-economic and technological problems, including regional disparities in development.